Serum selenium predicts achievement of full-dose cisplatin in concurrent chemoradiotherapy for locally advanced head and neck squamous cell carcinoma: A prospective, observational study. (October 2021) - Ohkoshi, Akira; Ishii, Ryo; Wakamori, Shun; Nakayama, Yuki; Yoshida, Takuya; Higashi, Kenjiro; Nakanome, Ayako; Ogawa, Takenori; Katori, Yukio
Highlights: Selenium deficiency is a potential therapeutic target in head and neck cancer. Selenium deficiency affects the achievement of full-dose cisplatin in CCRT. Baseline renal function affects the achievement of full-dose cisplatin in CCRT. Abstract: Objective: Concurrent chemoradiotherapy (CCRT) with three-weekly high-dose cisplatin (100 mg/m 2 ) is a standard treatment for locally advanced head and neck squamous cell carcinoma (HNSCC), but compliance with cisplatin is often poor due to various adverse events. The aim of this prospective, observational study was to determine the predictors of achievement of full-dose cisplatin. Methods: A prospective, observational study was conducted involving 60 patients who received CCRT with three-weekly high-dose cisplatin (100 mg/m 2 ) for locally advanced HNSCC. Possible predictors affecting compliance with cisplatin were subjected to univariate and multivariate logistic regression analyses. Age, sex, primary site, clinical stage, treatment intent, history of hypertension, diabetes mellitus, smoking and drinking habits, body mass index, creatinine clearance, serum albumin, controlling nutrition status, trace elements (Fe, Zn, Cu, Se), acute kidney injury, white blood cell count decrease, neutrophilia, and weight loss were the variables evaluated. Results: Twenty-seven patients achieved full-dose cisplatin (300 mg/m 2 ), and the other 33 patients did not. Multivariate logistic regression analysis showed that both mild renal dysfunction and selenium deficiency before treatment independently had negative impacts on achievement of full-dose cisplatin. Conclusions: As well as renal function, selenium deficiency is a potential therapeutic target for CCRT with high-dose cisplatin in HNSCC patients.